Differentiated Instruction: Analysis of Primary School Teachers’ Experiences in Amhara Region, Ethiopia - Merawi, Tadesse Melesse (Bahir Dar Journal of Education, 2020)
The main purpose of this study was to investigate primary school teachers’ practice of Differentiated Instruction (DI). For this study, a sequential mixed methods design was utilized. and data were collected from randomly selected primary school teachers, school principals, students and woreda education officers using questionnaire, interview, FGD and observation. Data were analyzed quantitatively using mean, standard deviation, one sample t-test, independent samples t-test, and one-way ANOVA and qualitatively through descriptions and narrations. The main findings of the quantitative data revealed that the majority of primary school teachers have limitations in practicing DI. Many teachers teach diversified learners in the same classroom in a form of ‘one-size-fits all’ approach. However, significant differences were scrutinized based on qualification, in-service training, and teaching experience in executing the content, process, learning environment, and product differentiations. In other words, degree holder teachers, teachers who participated in in-service training on DI, and experienced teachers (teachers of 10-20 years of teaching experience) practiced DI better than their counterparts. Similarly, the qualitative findings revealed that teachers’ practice of both content differentiation and product differentiation were lower than process and learning environment differentiations. Knowledge and training gaps of teachers, scarce school facilities, low commitment of teachers, weak school leadership support, and lack of favorable school environment were the major impeding factors. Therefore, it is timely to devise mechanisms to strengthen in-service capacity building training for teachers to effectively execute DI so as to address the diversified interests, readiness and learning profiles of students.